A novel 3′ untranslated region mutation in the SLC29A3 gene associated with pigmentary hypertrichosis and non‐autoimmune insulin‐dependent diabetes mellitus syndrome. Issue 4 (2nd April 2019) - Riachi, Melissa; Bas, Firdevs; Darendeliler, Feyza; Hussain, Khalid
Abstract : Background: Pigmentary hypertrichosis and non‐autoimmune insulin‐dependent diabetes mellitus (PHID) is one of the rare H syndrome diseases mainly characterized by hyperpigmentation, hypertrichosis, sensorineural hearing loss, cardiac complications, developmental delay, and diabetes mellitus (DM). Mutations in the coding regions of the SLC29A3 gene that encodes for an equilibrative nucleoside transporter (ENT3) have been reported to cause the phenotypic spectrum of the H syndrome. Disease‐causing mutations in the untranslated regions (UTRs) of the SLC29A3 gene have not been previously described in the literature. The aim of the study is to describe and assess the pathogenicity of a novel 3'UTR mutation in the SLC29A3 gene associated with the PHID phenotype in two Turkish patients. Methods: The mutation was identified by a targeted gene approach. To understand the pathogenicity of this 3'UTR mutation, RNA and protein expression studies were performed by using the quantitative real‐time polymerase chain reaction method and western blotting, respectively, using fibroblasts cultured from the patients' skin biopsies. Results: SLC29A3 and ENT3 expression levels were both decreased in the patients compared to controls matched for passage numbers, RNA, and protein extraction methods. Conclusions: A novel 3'UTR mutation in the SLC29A3 gene is associated with the PHID syndrome, highlighting a potentially new pathological mechanism for this disease. The involvement of the 3'UTR has not been previously established in any of the H syndrome disease cluster or in any complex syndrome of DM.